Enhancing the Self: Amateur Bodybuilders Making Sense of Experiences With Appearance and Performance-Enhancing Drugs - Macho, Juraj; Mudrak, Jiri; Slepicka, Pavel (Frontiers in Psychology, 2021)
In this paper, we implemented a methodological framework of interpretative phenomenological analysis (IPA) and a theoretical conceptualization of multiple selves to explore the subjective accounts of six amateur bodybuilders using appearance- and performance-enhancing drugs (APEDs). The participants made sense of their bodybuilding careers and experiences with APEDs in a way that showed a multiplicity and complexity of reasons for using APEDs, which stemmed from tensions they perceived between the context of bodybuilding and other life domains. The participants’ reasons for the use of APEDs included not only enhancing their body, appearance and performance but also enhancing other subjectively important psychological characteristics, such as agency and self-control, the development of knowledge and expertise, sense of meaning, well-being, and quality of life. In the analysis, we integrated these themes through the concept of the “extraordinary self”, based on which our participants strived for self-actualization through bodybuilding and the use of APEDs. In the sense making of our participants, a potential “exit point” subverting their APED use emerged from a tension between such “extraordinary selves” and the “ordinary selves” through which they perceived APEDs as preventing them from living normal, balanced lives outside the context of bodybuilding. However, success in balancing the two selves also created the possibility of the future use of APEDs.